Multistakeholder platforms in transboundary waters: What do we know, and where should we go? - Lautze, Jonathan; Nehring, Ryan (International Food Policy Research Institute, 2025)
This policy brief synthesizes recent evidence on multistakeholder platforms (MSPs) in shared river basins and presents practical guidance for river basin organizations, development partners, and policymakers. It compares established basin-level MSP approaches across three basins (Nile, Zambezi, and Mekong) and describes how stakeholders in the Incomati and Maputo River Basins—shared across the Republic of South Africa, Eswatini, and Mozambique—built on these approaches to design their own MSP. This brief translates comparative evidence and field experience into a practical toolkit for advancing MSPs in shared basins.